MONOKULTURALISME DALAM TAYANGAN WEB SERIES ANIMASI ANAK NUSSA - Tristi, Muhammad Alzaki; Gusbet, Rani Attiqah (Universitas Gadjah Mada, 2024)
The objective of this study is to demonstrate how the concepts of monoculturalism are evident in the Nussa children's web series animations. Employing a qualitative approach, the research employed qualitative content analysis by examining five specific episodes from the Nussa Official YouTube channel. The qualitative content analysis employed a semiotic approach to dissect both explicit and implicit meanings. The basis for the content of monoculturalism is drawn from the concepts outlined in